Monarchia absolutna ludwika XIV. Nowe ścieżki badawcze - Grobelna, Paulina (Studia Europaea Gnesnensia, 2014)
The classical perception of French absolutism, which so far has been identified with the system of powerful rule of the monarch with only theoretical limitations, should be subject to revision. A reinterpretation of the manner of exercising power is inevitable, especially having adopted the approach where absolutist theory is confronted with the practice of rule. Such a perspective reveals practical limitations of the monarch’s power, which obstruct a full performance of prerogatives arising from the theory of absolutist rule. !e interests of historians in the issues relating to the functioning of a state yielded a new approach to Louis’ XIV absolutism, while the vast body of pertinent works creates a situation where it is easy to lose one’s bearings in the maze of equivocal answers. Through a brief summary of the major themes in conducted studies, the article aims to demonstrate the complexity of the problem that French absolutism represents today